Assessment of Effect of Employees' Motivation on Workers' Productivity: A Case Study of Selected Hotels in Ikeja Local Government Area of Lagos State, Nigeria - Olugbemi, Moyosore Titilope; Yangomodou, Oluwapamilerin Damola; Bashorun, Oluwafeyikemi Edith; Onasanya, Adewale Sesan; Aledare, Eladi Iyabo (NIU Journal of Humanities; Vol 7 No 3 (2022): NIU Journal of Humanities, Vol. 7 No. 3, September 2022DO - 10.58709/niujhu.v7i3.1533, 2022)
No doubt, employees are the most significant resources in any organization. Without them, the goals of the organization can hardly be achieved. The poor attitude of hotel management especially with regards to motivating their employees has been a major concern in industry and is severally reported to have adversely affected the quality of services rendered to customers and the level of turnover in the industry. This study examined the assessment of employeesâ€™ motivation on workersâ€™ productivity (a case study of selected hotels in Ikeja Local Government Area of Lagos State, Nigeria). A total of one hundred and one (101) respondents were randomly selected and interviewed for the study through a specially designed questionnaire. Descriptive statistics such as frequency counts, mean and percentages estimation were used in analyzing the study data while Chi-Square statistical tool was used in testing the study hypotheses. Results revealed that majority (65.3%) of the respondents were male between the ages of 31-40 years were 44.6%, 68.3% (majority) of the respondent were married and educated 69.3% , the average years of working experience of the respondents 56.4%  were 6-10 years , 55.4% of the respondents were promoted in the last two years and 56.4% (also majority) were in the junior workers' category with less than N 100,000 monthly remuneration and majority of the respondent (64.5%) were worked for 12hours per day. The most  effective fringe benefits being adopted by the hotels in the study area in terms of motivating their employees are sponsorship for personnel trainings, timely payment of salaries and bonuses, payment for extra time spent at work and  provision of accommodation  among others. In addition, treatment of workers with dignity and respect, access to health care facilities, annual presentation of awards and promotion exercise are extrinsic factors that influence hotel workers' motivation in the study area . The study concluded that there is a significant relationship between socio-economic characteristics of the workers and the effect of employees' motivation on workersâ€™ productivity in the study area . The study recommends that management should be meticulous in the area of motivating their employees by rewarding or celebrating them through annual promotion exercise and presentation of awards. Employers should also give their employees the opportunity to acquire more knowledge and skills by sponsoring them to study abroad in related fields. Moreover, other motivational tools such as free healthcare services, transportation allowance, accommodation allowance and hazard allowance should be duly paid to employees in order to improve their performances. Keywords: Motivation, Employee, Workers, Hospitality, Hotel, Productivity